THE ORIGINAL PROVISION REGARDING RESERVATION IN THE INDIAN CONSTITUTION AND THE SUB-CLASSIFICATION OF RESERVED CLASS ISSUE: AN ANALYTICAL STUDY - Tunte, Vijay; Boyewar, Yadav Baburao (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In all countries, some facilities are provided to the neglected, backward and deprived sections of the society to a greater or lesser extent. In order to come into the mainstream and contribute to the development of the society and the country, such facilities are needed to bring such sections of the society and to provide them justice. Alternatively, reservation has been provided for that. In India, constitutional provision has been made to provide reservation to certain sections of the society in the political, educational and service sectors for the upliftment of the deprived sections. The subject of reservation has always been controversial in India. Currently, various sections of the society are demanding reservation. Therefore, it is necessary to understand the original purpose behind the creation of reservation. In that regard, this research paper examines what reservation means? What is the original provision of reservation in the Indian Constitution? Subsequently, the decision given by the seven-judges Constitution Bench of the Supreme Court regarding the decision on sub-classification in reservation has created hope that the deprived sections will get equal justice. In this way, the effects of sub-classification of reservation have also been studied.